2021
DOI: 10.1186/s13052-021-01010-x
|View full text |Cite
|
Sign up to set email alerts
|

Formula feeding practice and associated factors among mothers with infants 0–6 months of age in Addis Ababa, Ethiopia: a community-based cross-sectional study

Abstract: Background Lack of exclusive breastfeeding during the first half-year of life is an important risk factor for childhood morbidity and mortality. Despite this, less than 40% of infants below 6 months are exclusively breastfed worldwide. This is because breastfeeding is declining and being replaced by formula feeding. Nowaday, formula feeding has become a more common practice in urban communities of developing countries. However, relatively little information is available regarding formula feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 28 publications
4
17
2
Order By: Relevance
“…According to the findings of a study done in Addis Ababa, hospital care and early commencement of breast milk expression are important to a mother's ability to produce breast milk for her preterm infant at discharge. Exclusive breastfeeding was linked with ANC follow-up, PNC attendance, counseling, and pregnancy intention [14,26,27]. In Gondar, maternal age was less than 19 years, mothers were civil servants, husbands were illiterate, it was the first pregnancy, there was no postnatal follow up, and women had little awareness of the benefits of nursing and the composition of breastmilk [21].…”
Section: Factors To Timely Initiation and Exclusive Breast Feedingmentioning
confidence: 99%
“…According to the findings of a study done in Addis Ababa, hospital care and early commencement of breast milk expression are important to a mother's ability to produce breast milk for her preterm infant at discharge. Exclusive breastfeeding was linked with ANC follow-up, PNC attendance, counseling, and pregnancy intention [14,26,27]. In Gondar, maternal age was less than 19 years, mothers were civil servants, husbands were illiterate, it was the first pregnancy, there was no postnatal follow up, and women had little awareness of the benefits of nursing and the composition of breastmilk [21].…”
Section: Factors To Timely Initiation and Exclusive Breast Feedingmentioning
confidence: 99%
“…During natural lactation, some masticatory muscles begin their maturation and positioning, such as the temporalis (activated in mandibular retrusion) (9), the lateral pterygoid (necessary during propulsion), the mylohyoid (mainly responsible for swallowing), and the masseters (activated in sucking mechanics) (10), the mylohyoid (mainly responsible for swallowing) and the masseters (activated in sucking mechanics) (10), while the orbicularis oris of the upper and lower lips guide the growth and development of the anterior region of the stomatognathic system (11), being responsible for the maturation of the masticatory muscles (12). The upper and lower orbicular orbicular orbicular orbicularis oculi are responsible for stimulating the development of the jaws and differentiating the temporomandibular joints, which helps to prevent the development of parafunctional oral habits and malocclusions (13).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the United Nations (UN) Office of the High Commissioner for Human Rights stated that breastfeeding is a human rights issue for both mothers and children and should be protected and promoted for the benefit of both. The introduction of local nutrient-rich complementary foods is recommended thereafter with continued breastfeed-ing for 2 years of age and beyond (9)…”
mentioning
confidence: 99%
“…Most organizations recommend breastfeeding for at least one year, and the WHO recommends a minimum of 2 years, but less than 40% of infants below the 6 months are exclusively breastfeeding worldwide [ 186 , 187 ]. Multiple investigations have demonstrated that breast feeding not only reduces the risk of death and disease in early life but has lasting health benefits through adult life [ 188 , 189 ]. Taye et al [ 189 ] assessed the Authors found that the educational status of mothers, timing of initiation breastfeeding, pre-lactal feeding, and delivery by cesarean section were significantly associated with formula feeding practice.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple investigations have demonstrated that breast feeding not only reduces the risk of death and disease in early life but has lasting health benefits through adult life [ 188 , 189 ]. Taye et al [ 189 ] assessed the Authors found that the educational status of mothers, timing of initiation breastfeeding, pre-lactal feeding, and delivery by cesarean section were significantly associated with formula feeding practice. Therefore, early initiation of breastfeeding, educating mothers about the risks associated with pre-lacteal feeding and supporting mothers who gave birth by cesarean section for exclusive breastfeeding should be encouraged at the community and institutional levels.…”
Section: Introductionmentioning
confidence: 99%